The bifurcation point of the oxygen reduction reaction on Au–Pd nanoalloys. (18th April 2016) - Staszak-Jirkovský, Jakub; Ahlberg, Elisabet; Panas, Itai; Schiffrin, David J.
Abstract : The oxygen reduction reaction is of major importance in energy conversion and storage. Controlling electrocatalytic activity and its selectivity remains a challenge of modern electrochemistry. Here, first principles calculations and analysis of experimental data unravel the mechanism of this reaction on Au–Pd nanoalloys in acid media. A mechanistic model is proposed from comparison of the electrocatalysis of oxygen and hydrogen peroxide reduction on different Au–Pd ensembles. A H2 O production channel on contiguous Pd sites proceeding through intermediates different from H2 O2 and OOH σ adsorbate is identified as the bifurcation point for the two reaction pathway alternatives to yield either H2 O or H2 O2 . H2 O2 is a leaving group, albeit reduction of H2 O2 to H2 O can occur by electrocatalytic HO–OH dissociation that is affected by the presence of adsorbed OOH σ . Similarities and differences between electrochemical and direct synthesis from H2 + O2 reaction on Au–Pd nanoalloys are discussed.